Pengaruh Ukuran Perusahaan, Likuiditas, dan Profitabilitas terhadap Audit Report Lag pada Perusahaan Semen yang Go Public di Bursa Efek Indonesia - Dian Noor Citra Perdana; Agus Setyo Utomo; Erna Wati (STIE Wijaya Mulya, 2022)
Timeliness in the submission of financial statements is very important for report users. Timeliness in the submission of financial statements can affect the relevance of the financial information presented. Information in financial statements is said to be relevant if the information is submitted in a timely manner and has benefits for users of financial statement information.This study aims to determine the effect of firm size, liquidity, and profitability on audit report lag in cement companies that go public on the Indonesia Stock Exchange.The results of the coefficient of determination test show that 9.9% of audit report lag is influenced by three variables, namely company size, liquidity, and profitability, while the remaining 90.1% is influenced by other variables outside of the research that has been done. From the calculation results obtained F value of 1.622 with a significance of 0.229 more than 0.05 which indicates that the variables of firm size, liquidity, and profitability have no significant effect simultaneously or together on audit report lag. While the results of the t test show that the variables of firm size, liquidity, and profitability partially have no effect on audit report lag with values of 1.851, 0.781, -1.329. Liquidity is not the most influential variable on audit report lag.Keywords : Audit Report Lag, Company Size, Likuidity, Profitability